Parametric Cyclic Voltammetric Analysis of an Electrochemical Aptasensor for Staphylococcus aureus Iron-Regulated Surface Determinant Protein A Detection - Shokoufeh Soleimani; Tracy Ann Bruce-Tagoe; Najeeb Ullah; Michael K. Danquah (Micromachines)
Rapid and reliable detection of pathogens requires precise and optimized analytical techniques to address challenges in food safety and public health. This study focuses on the parametric characterization of an electrochemical aptasensor for Staphylococcus aureus (S. aureus) iron-regulated surface determinant protein A (IsdA) using cyclic voltammetry (CV) analysis, which offers a robust method for evaluating electrode modifications and electrochemical responses. Key parameters were optimized to ensure maximum sensitivity, including an aptamer concentration of 5 μM, an incubation time of 4 h, a potential range from −0.1 to 0.9 V, and a scan rate of 0.05 V/s. The aptasensor achieved stability and peak performance at pH 7.5 and 25 °C. These conditions were critical for detecting the IsdA protein as a biomarker of S. aureus. The aptasensor applicability was demonstrated by successfully detecting S. aureus in food samples such as milk and apple juice with high specificity and reliability. Zeta potential measurements confirmed the layer-by-layer charge dynamics of the AuNPs-aptamer-IsdA system. This work emphasizes the importance of CV in understanding the performance of the electrochemical sensor, and supports the aptasensor as a practical, sensitive, and portable tool for addressing critical gaps in foodborne pathogen detection.